CD47 Expression in Natural Killer Cells Regulates Homeostasis and Modulates Immune Response to Lymphocytic Choriomeningitis Virus - Nath, Pulak Ranjan; Gangaplara, Arunakumar; Pal-Nath, Dipasmita; Mandal, Ajeet; Maric, Dragan; Sipes, John M.; Cam, Maggie; Shevach, Ethan M.; Roberts, David D. (Frontiers in Immunology, 2018)
CD47 is a ubiquitous cell surface receptor that directly regulates T cell immunity by interacting with its inhibitory ligand thrombospondin-1 and limits clearance of cells by phagocytes that express its counter-receptor signal-regulatory protein-α. Murine natural killer (NK) cells express higher levels of CD47 than other lymphocytes, but the role of CD47 in regulating NK cell homeostasis and immune function remains unclear. Cd47-/- mice exhibited depletion of NK precursors in bone marrow, consistent with the antiphagocytic function of CD47. In contrast, antisense CD47 knockdown or gene disruption resulted in a dose dependent accumulation of immature and mature NK cells in spleen. Mature Cd47-/- NK cells exhibited increased expression of NK effector and interferon gene signatures and an increased proliferative response to interleukin-15 in vitro. Cd47-/- mice showed no defect in their early response to acute Armstrong lymphocytic choriomeningitis virus (LCMV) infection but were moderately impaired in controlling chronic Clone-13 LCMV infection, which was associated with depletion of splenic NK cells and loss of effector cytokine and interferon response gene expression in Cd47-/- NK cells. Broad CD47-dependent differences in NK activation, survival, and exhaustion pathways were observed in NK cell transcriptional signatures in LCMV infected mice. These data identify CD47 as a cell-intrinsic and systemic regulator of NK cell homeostasis and NK cell function in responding to a viral infection.